Xanthohumol: An underestimated, while potent and promising chemotherapeutic agent in cancer treatment. (August 2022) - Vesaghhamedani, Shadi; Ebrahimzadeh, Farnoosh; Najafi, Elnaz; Shabgah, Omid Gohari; Askari, Elham; Shabgah, Arezoo Gowhari; Mohammadi, Hamed; Jadidi-Niaragh, Farhad; Navashenaq, Jamshid Gholizadeh
Abstract: Today, there is a growing interest nowadays in the use of herbal substances as cancer therapeutic agents. Over recent years, Xanthohumol (XTL) has been brought out as a prenylated chalcone that is found in hops ( Humulus lupulus ) and beer. XTL is being investigated for its potential properties, and it has been found to have various biological effects, including anti-microbial, anti-viral, and immunomodulatory. Other than these biological effects, it has also been found that XTL exerts anti-tumor effects. In the beginning, XTL, by modulating cell signaling pathways, including ERK, AKT, NF-κB, AMPK, Wnt/β-catenin, and Notch signaling in cancer cells, inhibits tumor cell functions. Moreover, XTL, by inducing apoptotic pathways, either intrinsic or extrinsic, promotes cancer cell death and arrests the cell cycle. Furthermore, XTL inhibits metastasis, angiogenesis, cancer stemness, drug resistance, cell respiration, etc., which results in tumor aggressiveness inhibition. XTL has low solubility in water, and it has been hypothesized that some modifications, including biotinylation, can improve its pharmacogenetic characteristics. Additionally, XTL derivates such as dihydroXTL and tetrahydroXTL can be helpful for more anti-tumor activities. Using XTL with other anti-tumor agents is another approach to overcome tumor cell resistance. XTL or its derivatives, it is believed, might provide novel chemotherapeutic methods in future cancer therapy.